LONG-TERM RESULTS OF PROCTECTOMY WITH THE RECONSTRUCTION OF THE SPHINCTER, LEVATOR AND RESERVES-STORAGE TANK WITH LOW RECTAL CANCER - S. R. Bashirov; M. N. Trifonov; V. I. Tikhonov; M. Yu. Grishchenko (Бюллетень сибирской медицины)
Proctectomy with total mesorectal excision, resection of the internal sphincter, deep portions of the external sphincter and reductionwas performed on nine patients aged from 38 to 74 years with adenocarcinoma of low rectal cancer (T2N0M0 (n = 4), T2N1M0 (n = 1), T3N0M1 (n = 3), T4N2M1 (n = 1)), located in 8–25 mm from an anus. Simultaneously, atypical resections of the liver were performed on two of the patients. In the perineal section of the reduced intestine a sphincter was created from a smooth muscle cuff, a levator from not free serous, and a muscular flap, fixed to a forward wall of the small basin, and a reservoir of cross stitched submucosa site formed after the formation of a levator.  5 of the patients (T2N0-1M0)had no disease advance 3–9 years. They were able to hold firm feces, but were less able to hold liquid feces, and sometimes didn’t hold intestinal gas or differentiate between feces and gas, but were capable of ignoring an urge to defecate and to detain a defecation (level of a fecal continence on a scale of "Wexner score" (11 ± 1) of points).